THE EFFECT OF COMPETITION BETWEEN INDOMARET AND ALFAMART TOWARD THE EXISTENCE OF TRADITIONAL TRADERS BASED ON THE LAW OF BUSINESS COMPETITON PERSPECTIVE - Tini Kartini (Fakultas Hukum Universitas Djuanda Bogor, 2017)
Recently, there consists a rapid growth of Indomaret and Alfamart.so thateffects the existence of traditional traders. Research objectives are as follow; firstly, to understand and to analyze the effect of competition between Indomaret and Alfamart toward the existence of traditional traders. Secondly, to understand and to analyze the government’s effort to redeem the effect. Research methodology which used is the combination of normative law research and empirical law research methodologies. Research outcomes are as follow; firstly, the negative effect is the traditional traders suffer turnover decline which subsequently lowers their profits.. On the contrary, the positive effect is the competition stimulates the traditional traders to improve the qualities of their products, service, facilities as well as innovation so they could have competitive abilities; the traditional traders could create employment for other micro business scheme to endeavor those of UMKMs. Secondly, the government’s effort to redeem the effect of competition between Indomaret and Alfamart toward the existence of traditional traders, is the policy of local regulation which specifically regulates licensing, localizing, and zone along with the analysis of social-economic of local society, including the existence of traditional traders.